Relações alométricas da Anomalocardia brasiliana (Gmelin, 1791) na praia de Mangue Seco, Pernambuco-Brasil - SOUZA, André Batista de (2011)
Anomalocardia brasiliana is one of the most common bivalve marine mollusks found in Pernambuco, in the Northeast of Brazil. This shellfish is mainly found on the northern coast of the region, where hand fishing has always been a traditional activity. The aim of the present study was to assess the allometric ratios of growth and weight of the shellfish A. brasiliana, on Mangue Seco beach, in northern Pernambuco. Non-linear regression was performed (Gauss Newton methodology) to investigate if the shellfish exhibited positive, negative or isometric allometry using the following measurements: length/width; length/height; width/height; weight of the shell/soft tissue weight and length/weight (total, shell and soft tissue). Analysis of A. brasiliana confirmed that the length/width ratio was positively allometric whereas all other ratios were negative. The results of the present study may be used in the preparation of management plans for fishing and mariculture development and as a basis to diagnose possible effects caused by environmental changes.